2014
DOI: 10.1002/pssb.201350206
|View full text |Cite
|
Sign up to set email alerts
|

All‐electrical detection of spin Hall effect in semiconductors

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.Since the prediction of the spin Hall effect more than 40 years ago, significant progress was made in theoretical description as well as in experimental observation, especially in the last decade. In this article, we present three different concepts and measurement geometries for all-electrical detection of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…With this, we found to be ~ 0. is very difficult to satisfy this condition experimentally, spin Hall angle values might not be truly extracted with the existing theory. Similar to our case, a recent study using the same theory for extracting the spin Hall angle found much larger values than the theoretically predicted values [27]. Further theoretical studies that satisfy the experimental conditions are required for the more accurate values.…”
supporting
confidence: 85%
“…With this, we found to be ~ 0. is very difficult to satisfy this condition experimentally, spin Hall angle values might not be truly extracted with the existing theory. Similar to our case, a recent study using the same theory for extracting the spin Hall angle found much larger values than the theoretically predicted values [27]. Further theoretical studies that satisfy the experimental conditions are required for the more accurate values.…”
supporting
confidence: 85%
“…19 We find a ratio of 5 Â 10 À3 for a photon energy of 1.53 eV and a carrier density of $3.8 Â 10 17 cm À3 . This ratio agrees well with the results of an all-electrical study of the spin Hall effect in n-doped GaAs by Ehlert et al, 27 who obtained a value of $10 À3 for the spin Hall angle.…”
supporting
confidence: 91%
“…The detecting method is commonly based on the ISHE, where the Hall voltage is induced by spin current. Many experimental setups are described in literature [138,141,[149][150][151][152][153][154], which use various nonmagnetic materials, including normal metals, superconductors, nanotubes etc.…”
Section: Detecting By Electrical Methodsmentioning
confidence: 99%
“…Two different approaches are mainly used for nonlocal electric detecting of SHE: (1) detecting the "direct SHE" i.e. spin accumulation at two edges of a sample due to SOI, under flow of charge current of unpolarized carriers, and detecting spin magnetization accumulated at the edges with ferromagnetic potential contacts [141,153,155], and (2) detecting the "inverse SHE" (ISHE) by injection of polarized charge carriers via ferromagnetic current contacts and by detecting unbalance in spin accumulation at the edges with nonmagnetic potential contacts [152,[156][157][158].…”
Section: Detecting By Electrical Methodsmentioning
confidence: 99%
See 1 more Smart Citation